Republic of Tajikistan : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2003)
This Selected Issues paper and Statistical Appendix examines banking sector developments in the Republic of Tajikistan. The paper estimates quasi-fiscal activities in the energy sector, and provides an assessment of external sector trade and the need for further trade reform. Developments in the agriculture sector are assessed. The paper highlights that the lessons that emerge from recent experience indicate that weak institutions in Tajikistan have resulted in erratic implementation of structural reforms, which threaten the sustainability of the economy's improved macroeconomic stability.